2022
DOI: 10.3389/fpsyg.2022.804792
|View full text |Cite
|
Sign up to set email alerts
|

Infant-Directed Speech From a Multidimensional Perspective: The Interplay of Infant Birth Status, Maternal Parenting Stress, and Dyadic Co-regulation on Infant-Directed Speech Linguistic and Pragmatic Features

Abstract: Infant-directed speech (IDS), the particular form of spontaneous language observed in interactions between parents and their infants, is a crucial aspect of the mother-infant interaction and an index of the attunement of maternal linguistic input to her infant communicative abilities and needs during dyadic interactions. The present study aimed to explore linguistic and pragmatic features of IDS during mother-infant interactions at 3-month of infant age. The effects of infant (birth status: preterm vs. full-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
3
4
0
Order By: Relevance
“…The literature on the impact of prematurity on parental stress levels has reported conflicting results to date. Indeed, while some studies indicated a significant impact of prematurity on maternal stress [30,32], others did not highlight differences between PT and FT populations [33,36,37,63]. Our finding aligned with this latter series of studies suggesting…”
Section: Maternal Parenting Stress At 3 and 9 Monthssupporting
confidence: 88%
See 4 more Smart Citations
“…The literature on the impact of prematurity on parental stress levels has reported conflicting results to date. Indeed, while some studies indicated a significant impact of prematurity on maternal stress [30,32], others did not highlight differences between PT and FT populations [33,36,37,63]. Our finding aligned with this latter series of studies suggesting…”
Section: Maternal Parenting Stress At 3 and 9 Monthssupporting
confidence: 88%
“…The presence of parental postpartum symptomatology and higher levels of parenting stress can adversely impact the quality of early dyadic interactions [27,32,33], including the quality of early dyadic exchanges between mothers and their infants, in terms of interactive behaviors [14,18,[34][35][36] and verbal input directed towards the infant [15,37]. Consequently, these difficulties have the potential to result in more negative outcomes for infant development [34,38].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations